Penanaman Mangrove Berbasis Ekoteologi dan Sosial di Desa Tumbak Madani: Mangrove Plantation Program Based on Eco-Theological and Social Approaches in Tumbak Madani Village - Asma, Andi; Asy'arie, Novia Kurniasari; Aslah, Siti Nurzain; Toligaga, Ifra Meilani; Juliana, Dita; Lantong, Tirza Anastasia; Mamonto, Tria Ananda; Abrori, M. Faiz; Rauf, Fatmawati; Baginda, Syahril; Husna, Elfira Shofia (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This community service activity focuses on efforts to preserve the coastal ecosystem through mangrove planting in Tumbak Madani Village, Southeast Minahasa Regency. The program was designed with an ecotheological and socio-cultural approach, integrating religious values, environmental awareness, and the local wisdom of coastal communities. The planning stage involved coordination with the village government to determine the planting location, collect seedlings, and formulate implementation strategies. A total of 110 mangrove seedlings were successfully collected from naturally fallen propagules around the coastal area. The activity began with a socialization session on the ecological benefits of mangroves, including their role in coastal protection against abrasion, as wave barriers, and as marine habitats, as well as their economic potential as tourism attractions and as processed products. The program then continued with the planting of seedlings at intervals of about one meter, carried out in a spirit of cooperation among the community, the village government, and participants. The outcomes of this service activity indicated an increase in community awareness regarding the importance of conserving mangrove ecosystems and the establishment of cross-sector collaboration in environmental preservation. This program is expected to serve as an initial step toward strengthening ecotheological and socio-cultural movements in maintaining the sustainability of coastal environments.